Comparing Cisplatin Dosing Schedules in Concurrent Chemoradiotherapy for Locally Advanced Head-and-Neck Cancer: A Comprehensive Review of Weekly Versus 3-Weekly Regimens - Oscar Chi-Yu Yang; Nai-Wen Su; Yi-Shing Leu; Yi-Fang Chang (Journal of Cancer Research and Practice)
Objective: There are approximately 900,000 new cases of head-and-neck cancer (HNC) annually, with a significant proportion presenting as locally advanced head-and-neck cancer (LA-HNC). Cisplatin-based concurrent chemoradiotherapy (CCRT) has become widely accepted, particularly for patients deemed inoperable. The standard regimen is a high-dose 3-weekly cisplatin schedule, however, this can lead to considerable toxicities. This review evaluates the efficacy, safety, and compliance associated with an emerging alternative: a weekly cisplatin dosing schedule. Data Sources: The review of current literature included randomized controlled trials, meta-analyses, and retrospective studies within the past decade, comparing weekly, and 3-weekly cisplatin CCRT regimens for LA-HNC. Study Selection: Studies comparing 3-weekly and weekly cisplatin-based CCRT were included. Results: Weekly cisplatin regimens demonstrated comparable efficacy to the traditional 3-weekly schedule, with lower toxicity and improved compliance. Key studies suggested that weekly cisplatin may have a more favorable safety profile, with reduced risks of neutropenia, renal impairment, and ototoxicity. However, the potential for slightly better locoregional control with the 3-weekly regimen remains a point of ongoing investigation. Novel agents including immune checkpoint inhibitors, xevinapant, and berzosertib are being actively investigated as combinational therapies with cisplatin-based CCRT. Conclusion: Weekly cisplatin-based CCRT is a viable alternative to the traditional 3-weekly regimen for treating LA-HNC, particularly in patients at higher risk of toxicities. Further randomized controlled trials are required to confirm the optimal cisplatin schedule and efficacy of combinational therapies with novel agents. These findings underline the importance of exploring treatment protocols that balance therapeutic benefits with reduced adverse effects and improved compliance.